When algorithms write literature: A comparative study of Sally Rooney’s Mr Salary and its AI simulation - Adel, Mohammed A.; Elhalafway, Ayman; Ismail, Sarah; Mahamed, Ahmad M. Al; Khalifa, Samir (Research Journal in Advanced Humanities, 2026)
This research examines the interplay between human creativity and artificial intelligence by comparing Sally Rooney’s short tale, Mr Salary (2019), with an AI-generated synthesis of the work. As generative AI gains prominence as a source of creation, this study highlights the pressing need to assess not only the technical capabilities of authorship but also the ramifications of algorithmic processes on ethical, literary, and cultural dimensions. The present research mostly offers either a technical or abstract examination of the phenomenon of AI writing; few instances have been noted that conduct in-depth analyses on the construction of consciousness and meaning in machine-generated text. This gap is what drives the current writing. The study employs a close-reading approach that is qualitative in nature, based on simulation theory, posthumanism, as well as adaptation theory. It argues about narrative voice, style, thematic development, emotional restraint, and psychological realism of the two studies. The findings suggest that certain superficial stylistic patterns (structural coherence, rhythm) are already grasped by the AI, yet, it is incapable of preserving the embeddedness of the culture, being deliberately vague and attaining profundity of emotion. The semblance of literariness is demonstrated in the text of AI in contrast with creative consciousness. The paper concludes that eventually human umbilical authorship is abandoned to allow a force of lived experience, emotional intentionality, and interpretive silences that can never be reduced to algorithmic predictability. The study recommends further investigation of AI-generated literature with a focus on the ethics, authorship, and meaning of mechanisms of creativity.